A Facile Route to Cesium Lead Bromoiodide Perovskite Microcrystals and Their Potential Application as Sensors for Nitrophenol Explosives. Issue 31 (24th August 2017) - Aamir, Muhammad; Khan, Malik Dilshad; Sher, Muhammad; Bhosale, Sheshanath V.; Malik, Mohammad Azad; Akhtar, Javeed; Revaprasadu, Neerish
Abstract : To achieve a material with pure phase and crystallinity, the use of antisolvents is found to be crucial. Herein, we report the synthesis of phase‐pure CsPbBr2 I microcrystals with defined morphologies by using trioctylphosphine (TOP) as an antisolvent and capping agent. The as‐prepared inorganic perovskite has enhanced thermal stability and promising optical properties, displaying a band gap of 2.2 eV. The photoluminescence (PL) studies suggest high sensitivity of the as‐prepared inorganic perovskites against nitrophenols, which makes them a potential candidate for the detection of nitrophenol. Abstract : We report the synthesis of CsPbBr2 I by an antisolvent method using tri‐ n ‐octylphosphine (TOP) as both the antisolvent and surfactant to produce pure‐phase microcrystals with defined morphologies. The as‐prepared microcrystals display enhanced thermal stability and promising optical properties. They were found to be an efficient fluorescent probe for the detection of trinitrophenol.